Search for heavy resonances decaying into a vector boson and a Higgs boson in final states with charged leptons, neutrinos, and b quarks - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (PHYSICS LETTERS B, 2017)
A search for heavy resonances decaying to a Higgs boson and a vector boson is presented. The analysis is performed using data samples collected in 2015 by the CMS experiment at the LHC in proton–proton collisions at a center-of-mass energy of 13 TeV, corresponding to integrated luminosities of 2.2–2.5 fb−1. The search is performed in channels in which the vector boson decays into leptonic final states (Z→ννZ→νν, W→νW→ν, and Z→Z→, with =e,μ=e,μ), while the Higgs boson decays to collimated b quark pairs detected as a single massive jet. The discriminating power of a jet mass requirement and a b jet tagging algorithm are exploited to suppress the standard model backgrounds. The event yields observed in data are consistent with the background expectation. In the context of a theoretical model with a heavy vector triplet, a resonance with mass less than 2 TeV is excluded at 95% confidence level. The results are also interpreted in terms of limits on the parameters of the model, improving on the reach of previous searches.